Luther and Calvin, and The Christian Work Ethics - Naomi Sampe; Novita Toding; Hasrath Dewi Ranteallo (Institut Agama Kristen Negeri Toraja, 2021)
The aim of this research is to explain and describe the relationship between reformed theology and the reform of European Christians' views on the nature of the church in life as followers of Jesus. The aim of this research is to explain and describe the relationship between reformed theology and the reform of European Christians' views on the nature of the church in life as followers of Jesus. The research method used is qualitative with data collection techniques, literature studies and data analysis is descriptive qualitative. The results showed that Luther's theology of vocations in all areas of life and Calvin's theology of predestination, sanctification, and justification became the basis for changes in the work ethic of European society at that time. They see work and the results of work are part of faith, therefore they work hard, value time, and appreciate the results of work or material. Therefore, work and work are part of the life of faith. In later developments, there was an excessive appreciation of material or capitalism because of the secularization of work culture, which was originally part of faith. In fact, this Capitalism is not in accordance with Christian ethics. Penelitian ini bertujuan untuk menjelaskan dan mendeskripsikan hubungan antara teologi reformator dengan pandangan orang Kristen Eropa reformasi tentang hakikat gereja dalam kehidupan sebagai pengikut Yesus. Tujuan dari penelitian ini adalah untuk menjelaskan dan mendeskripsikan hubungan antara teologi reformator dengan pandangan orang Eropa Kristen tentang hakikat gereja dalam kehidupan sebagai pengikut Yesus. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data, studi kepustakaan dan analisis data adalah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa teologi panggilan Luther di segala bidang kehidupan dan teologi predestinasi, pengudusan dan pembenaran Calvin menjadi dasar perubahan etos kerja masyarakat Eropa saat itu. Mereka melihat kerja dan hasil kerja adalah bagian dari iman, oleh karena itu mereka bekerja keras, menghargai waktu dan menghargai hasil kerja atau materi. Jadi bekerja adalah bagian dari kehidupan iman. Dalam perkembangan selanjutnya, terjadi apresiasi yang berlebihan terhadap material atau kapitalisme karena sekularisasi budaya kerja yang semula merupakan bagian dari keimanan. Padahal, Kapitalisme ini tidak sesuai dengan etika Kristen.